The effect of Enalapril drug on some histological aspects of testes tissue in the mature albino male mice - Moosa, Abeer Uthman; Ali, Dina khudhair Hussein (Iraqi Journal of Science, 2018)
The study aimed to evaluate whether Enalapril has any effects on the testicular tissue of the albino male mice which received or did not receive treatment with Enalapril.Mature mice were divided into three groups: control group which fed with 0.1mg of normal saline, the second group was orally fed with 10 mg/Kg of Enalapril drug while the third group was fed with 20 mg/Kg of drug, one time a day for 30 successive days by using gavage tube (0.1ml). The histological sections were performed and the slides were examined using the light microscope. The present study result of light microscopic images of mice testes cross sections which treated with 20 mg/Kg of Enalapril showed coagulated necrosis on spermatogonia germ cells, stopping the maturation in testicular tissue and ischematic alternations. Furthermore, the group treated with 10 mg/Kg showed arresting of spermatozoa maturation, congestion of blood vessels and spreading of edema. In comparison with the control group which demonstrated normal interstitial tissue and absence of edema with spermatogenic maturation observing numerous spermatozoa within the tubule lumen. In conclusion, Enalapril might play a role in pathogenesis of testicular tissue and men infertility.